RISIKO DAN PENGEMBALIAN HASIL PADA INVESTASI DEPOSITO MUDHARABAH BANK SYARIAH - Nur Wahyu Ningsih; Karnila Ali (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2021)
The research objective is to determine the risk of mudharabah deposit investment in Islamic banking measured by the VaR approach and to determine the rate of return on bank investment using mudharabah bank deposit funds measured by the RAROC approach. This type of research is a quantitative study and uses the VaR and RAROC measurement techniques. It is indicated that long-term investment using mudharabah deposits is more risky than short-term investments, this is indicated by the level of change in monthly returns that fluctuates significantly. But customers prefer long-term investments in mudharabah deposits marked by the amount of 12-month deposit funds that reach 35.63% of the total mudharabah deposit funds managed by the bank. This indicates that the customer chooses a long-term risk in order to get the maximum benefit. Risk Adjusted Return On Capital (RAROC) analysis describes the level of income earned by Islamic banks that has been adjusted to the risks that will occur, this shows that the income earned by the bank has not been able to cover the possible potential losses that will occur. The RAROC result shows the following figures for each year 20, -19, -4. The RAR value shows a positive overall number, which indicates that the bank is considered capable of controlling risks that can erode bank capital.